Current Status of Biosimilar Growth Hormone - Saenger, Paul (Hindawi Publishing Corporation, 2009)
As the first wave of biopharmaceuticals is set to expire, biosimilars or follow-on protein products (FOPPs) have emerged. The regulatory foundation for these products is more advanced and better codified in Europe than in the US. Recent approval of biosimilar Somatropin (growth hormone) in Europe and the US prompted this paper. The scientific viability of biosimilar growth hormone is reviewed. Efficacy and safety data (growth rates, IGF-1 generation) for up to 7 years for pediatric indications measure up favorably to previously approved growth hormones as reference comparators. While the approval in the US is currently only for treatment of growth hormone deficiency (GHD) in children and adults, the commercial use of approved biosimilar growth hormones will allow in the future for in-depth estimation of their efficacy and safety in non-GH deficient states as well.